2018
DOI: 10.3389/fphys.2018.00652
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Values of Long Non-coding RNAs in Bladder Cancer: A Systematic Review

Abstract: Background: Increasing evidence shows that dysregulated expression of long non-coding RNAs (lncRNAs) can serve as diagnostic or prognostic markers in bladder cancer. The aim of this study was to evaluate the clinical values of dysregulated lncRNAs in bladder cancer.Methods: Eligible studies were systematically searched in PubMed, Embase, and Web of Science databases from inception to December 2017. Odds ratios (OR) were calculated to investigate the correlation between lncRNAs and clinicopathological parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…For instance, the MALAT1 expression level was associated with lymph node metastasis and poor survival rate of UCC patients. LncRNA urothelial cancer-associated 1 (UCA1) showed the diagnostic value for UCC of the bladder [15]. Both in vivo and in vitro studies have shown that MALAT1 can promote migration and metastasis of bladder cancer through inducing EMT [36,37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the MALAT1 expression level was associated with lymph node metastasis and poor survival rate of UCC patients. LncRNA urothelial cancer-associated 1 (UCA1) showed the diagnostic value for UCC of the bladder [15]. Both in vivo and in vitro studies have shown that MALAT1 can promote migration and metastasis of bladder cancer through inducing EMT [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…In urothelial bladder carcinoma, approximately 50 lncRNAs were found to be aberrantly expressed and were shown to have prognostic and diagnostic values [15]. For example, metastasis-associated lung adenocarcinoma transcript-1 (MALAT1) was reported to associate with lymph node metastasis and poor overall survival.…”
Section: Introductionmentioning
confidence: 99%
“…The regulatory ncRNAs are broadly subcategorized into microRNAs (miRNAs, 18-25 nt), small interfering RNAs (siRNAs, <200 nt), piwi-interacting RNAs (piRNAs, <200 nt), and long noncoding RNAs (lncRNAs, >200 nt) [11]. Emerging studies on regulatory ncRNAs have shown their role as biomarkers or physiological regulators in many types of cancers, such as breast cancer, osteosarcoma, lung cancer, hepatocellular carcinoma, cervical cancer, bladder cancer [12][13][14][15][16]. Moreover, there have been increased investigations into the role of ncRNAs in ESCC [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al [22] reported that expression of SPRY4-IT1 in bladder cancer tissues and bladder cancer cell lines was higher than that in paracancerous normal tissues and normal bladder epithelial cells. Downregulation of SPRY4-IT1 expression by siRNA interference significantly inhibited the proliferation and migration of bladder cancer cells and promoted apoptosis of bladder cancer cells [23]. To date, little is known about the role of LINC00612 in tumors.…”
Section: Discussionmentioning
confidence: 99%